The occurrence of schistosomus reflexus in bovine dystocia. - KIPOURIDIS (Κ. ΚΗΠΟΥΡΙΔΗΣ), K.; KARAGIANNIDIS (Α. ΚΑΡΑΓΙΑΝΝΙΔΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The literature concerning incidence and etiology of schistosomus reflexus in domestic animals is reviewed and an interesting case of dystocia in a twin pregnancy (with a normal and a schistosomus reflexus fetus) is described. Examination of the reproductive records in 210 dairy cow units of Pentalofos region with 10000 cows approximately during a 17-year period (1982-1999) showed that in 2050 cases of bovine dystocia attended, only 1 (0.05%) was caused by schistosomus reflexus and treated by Caesarean section.